FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PERBANKAN PADA BANK UMUM YANG GO PUBLIC DI INDONESIA PERIODE 2010-2012 - Harlinda Yustika Putri, 11.05.62.0011; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to determine the Factors Affecting the Distribution of Commercial Bank Credit Banking Go Public in Indonesia 2010-2012 period. The population in this study is a banking company that is listed on the Indonesia Stock Exchange 2010-2012. The samples in this study were taken by purposive sampling method. Data were analyzed by using the skewness-kurtosis test for normality, the classic assumption test, test coefficient of determination, F-test and test hypotheses. The results of this study are the first hypothesis is obtained that does not affect the CAR variable credit, the second hypothesis that the variable ROA obtained significant positive effect on credit, the third hypothesis that the variables NPL obtained significant negative effect on credit, the fourth hypothesis that the variable deposits obtained significant positive effect on credit , earned fifth hypothesis that the variable BI RATE not negatively affect credit, earned sixth hypothesis that the variable does not affect the credit LDR.Keywords: Credit, CAR, ROA, NPL, DPK, BIRATE, LDR